2000
DOI: 10.1080/713671106
|View full text |Cite
|
Sign up to set email alerts
|

Equity and Advocacy Expectations of Culturally Diverse Families’ Participation in Special Education

Abstract: The authors contend that the equity and advocacy expectations imbedded in the legal mandate for parent participation in the special education decision-making process directly contradict the hierarchy of professional status and knowledge on which the positivist paradigm of professionalism is based, and are also in con ict with the values held by many families from culturally diverse backgrounds, contributing to low levels of participation and advocacy. They argue the need for professional education to incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
159
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 30 publications
3
159
0
4
Order By: Relevance
“…Although each of these steps represents an improvement, the system and the professionals within it still hold the power by defining how and when parents are involved (Harry, 1992a). This imbalance in power is especially apparent between culturally and linguistically diverse families and school personnel (Kalyanpur, Harry, & Skrtic, 2000;Salas, 2004).…”
Section: The Role Of Parents In Special Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although each of these steps represents an improvement, the system and the professionals within it still hold the power by defining how and when parents are involved (Harry, 1992a). This imbalance in power is especially apparent between culturally and linguistically diverse families and school personnel (Kalyanpur, Harry, & Skrtic, 2000;Salas, 2004).…”
Section: The Role Of Parents In Special Educationmentioning
confidence: 99%
“…Although each of these steps represents an improvement, the system and the professionals within it still hold the power by defining how and when parents are involved (Harry, 1992a). This imbalance in power is especially apparent between culturally and linguistically diverse families and school personnel (Kalyanpur, Harry, & Skrtic, 2000;Salas, 2004).One of the difficulties in establishing collaborative relationships may be related to educators' lack of understanding of family culture or unwillingness to investigate the meaning behind certain behaviors. Through a series of qualitative interviews, Harry (1992a) found that African American parents' appearance of apathy and disinterest in their child's education was masking parents' mistrust of education professionals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The need to advocate for children with special needs is more pronounced than for typically developing children (Mlawer, 1993). This advocacy expectation may be explicit, as with early intervention programs that prepare parents to be advocates for their children (Wang et al, 2004), or implicit in the design of policies that require parents to initiate the process of securing services for their children (Kalyanpur, 2000). Beneath this advocacy expectation is the assumption that parents have the time, interest, and inclination to assume this advocacy role, as well as the knowledge and skills to function within this role (Turnbull & Leonard, 1981).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…This can be especially difficult for parents with cultural orientations that highly esteem professionals; some cultures perceive professionals as a source of unquestionable knowledge and parents may not expect to be treated as an equal and collaborator in making decisions on behalf of their child. Moreover, the level of assertiveness needed for advocacy can conflict with cultural norms (Kalyanpur, 2000).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%